Restoration and Reaction: Reinterpreting the Marian Church - Freeman, Thomas S. (The journal of ecclesiastical history, 2018)
Although the reign of Mary i (1553-8) was a tumultuous and eventful one, for over four hundred years there was little debate about it or about the queen's efforts to restore Catholicism to England. The reign was almost universally perceived as poor, nasty, brutish and short-lived and the restoration of Catholicism was believed to have been doomed to failure, both because the burning of heretics offended English sensibilities and because Protestantism was already so deeply embedded in England that it could not be uprooted. Yet towards the end of the twentieth century, the tectonic plates of historical research began to shift and the resulting tremors altered the historiographical landscape of Mary's reign, and indeed of the English Reformation.